Bibliometric Analysis of Character Education Development Maps in The Scopus Database - Ambarwati, Andreana Putri; Jinan, Mutohharun; Azani, Mohammad Zakki; Apriantoro, Muhamad Subhi; Ashfahany, Afief El (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine the mapping of the development and direction of character education research in publications indexed by Scopus. This study used bibliometric analysis techniques to explore all publications indexed in the Scopus database on character education from 1962 to 2023. The data obtained were analysed using Excel and R/R-Studio. VOSviewer is used to visually analyse the simultaneous occurrence of keywords and document citations. The authors found 1,028 publications that fit the function, subject, and criteria set. The results of this study showed an annual growth rate of 9.26%, with the most publications on character education in 2021. The United States is the country that contributes the most publications with affiliations from Universitas Pendidikan Indonesia. Supriyadi T became the most prolific writer in character education development. The bibliometric analysis performed was limited to Scopus data. Other national and international databases should have been considered in the study. This study presents a brief overview of the literature accessible to character researchers and provides recommendations for future research.